2015
DOI: 10.1097/iae.0000000000000306
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Preoperative Medical Testing for Vitreoretinal Surgery

Abstract: Incidence of postoperative systemic adverse events after vitreoretinal surgery was 4% and was significantly increased in patients with coronary artery disease, asthma, chronic renal disease, or receiving general anesthesia. In this series, preoperative testing did not measurably influence rates of postoperative systemic complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
12
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 9 publications
3
12
3
Order By: Relevance
“…In a recent paper, the most common systemic comorbidities of VR surgical patients were hypertension (53%), diabetes mellitus (37%) and coronary artery disease (18%) (Shalwala et al 2015). In our study, however, these systemic diseases were less common among the patients.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…In a recent paper, the most common systemic comorbidities of VR surgical patients were hypertension (53%), diabetes mellitus (37%) and coronary artery disease (18%) (Shalwala et al 2015). In our study, however, these systemic diseases were less common among the patients.…”
Section: Discussioncontrasting
confidence: 66%
“…In our study, however, these systemic diseases were less common among the patients. Shalwala et al (2015) also reported significantly increased incidence of postoperative systemic adverse events after VR surgery in patients with coronary artery disease, asthma, chronic renal disease or in patients operated under general anaesthesia. Unfortunately, in our study, the documented register data did not allow us to analyse systemic adverse events among the cohort.…”
Section: Discussionmentioning
confidence: 94%
“…[ 7 , 8 ] In addition, patients undergoing vitreoretinal surgery may have greater comorbidities such as renal disease and coronary artery disease, which was associated with a significant increase of postoperative systemic adverse events after vitrectomy. [ 21 ] Thus, an optimal anesthesia method for rapid and adequate recovery with minimal complications should be selected to perform vitrectomy with general anesthesia successfully, especially if performed under ambulatory setting.…”
Section: Discussionmentioning
confidence: 99%
“…The study of preoperative medical testing in vitreoretinal surgery has been much more limited. To date, a single retrospective study has evaluated the role of preoperative testing in postoperative systemic complications in all cases of vitreoretinal surgery performed at a single center 5. Shalwala et al showed postoperative adverse systemic events in 4% of the cases, with an increased risk among patients receiving general anesthesia and in patients with comorbidities including coronary artery disease, asthma, and chronic renal disease.…”
Section: Introductionmentioning
confidence: 99%